2011
DOI: 10.2218/ijdc.v6i2.193
|View full text |Cite
|
Sign up to set email alerts
|

Educating Digital Curators: Challenges and Opportunities

Abstract: This paper describes a number of critical challenges faced by digital curation educators and suggests how the choices we make in building educational programs may impact the development of curation as a professional discipline. We focus on curriculum and program building as key steps in defining the educational needs of curators, and we argue for greater collaboration among educators, researchers and practitioners in the field, as a way to speed the emergence of curation as a discipline and to foster the integ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Digital curation even seemed a potential locus for archival education (Cox 2012 ). Sundry graduate education initiatives, though often funded short-term and by soft-money, attested to this optimism (Anderson et al 2011 ; Bastian et al 2010 , 2011 ; Botticelli et al 2011 ; Fulton et al 2011 ; Galloway 2011 ; Gregory and Guss 2011 ; Harvey and Bastian 2012 ; Kelly et al 2013 ; Kim et al 2011 ; Lee 2009 ; Lyon and Brenner 2015 ; Mayernik et al 2015 ; Moen et al 2012 ; Palmer et al 2008 ; Renear et al 2009 ; Yakel et al 2011 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Digital curation even seemed a potential locus for archival education (Cox 2012 ). Sundry graduate education initiatives, though often funded short-term and by soft-money, attested to this optimism (Anderson et al 2011 ; Bastian et al 2010 , 2011 ; Botticelli et al 2011 ; Fulton et al 2011 ; Galloway 2011 ; Gregory and Guss 2011 ; Harvey and Bastian 2012 ; Kelly et al 2013 ; Kim et al 2011 ; Lee 2009 ; Lyon and Brenner 2015 ; Mayernik et al 2015 ; Moen et al 2012 ; Palmer et al 2008 ; Renear et al 2009 ; Yakel et al 2011 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…After reviewing literature on key digital curation projects described above, we found that these digital curation initiatives and education and training programs inconsistently use the term "competency", often interchangeably with "skills" and "abilities" without further explaining the context of these terms. For example, Botticelli et al (2011) described what they believe to represent a core curation knowledge base and key challenges in developing curation competencies. They suggested that one could think of a list of professional competencies as a "mission statement" for a digital curation program, though they did not specifically define or describe how they conceptualized the term "competency".…”
Section: The Concept Of Professional Competency In Digital Curationmentioning
confidence: 99%
“…Examples from recent literature include the need to balance technical skills with soft skills (de Smaele, Verbakel, Potters, & Noordegraaf, 2013) and organizational aspects with domain-specific aspects (Kim, Addom, & Stanton, 2011). Educators developing training initiatives have also acknowledged more immediate challenges that are symptomatic of this situation, such as defining the boundaries of the content to the covered, the rapid growth of literature in the field, and the lack of widely accepted best practices (Botticelli, Fulton, Pearce-Moses, Szuter, & Watters, 2011). The success of vocational training relies on educators navigating these competing needs in the design and delivery of their programmes.…”
Section: Strengths Of Existing Training Programmesmentioning
confidence: 99%